Comparison of physical preservation strategies for accurate characterization of the coffee fruit microbiome - Etztli Itzel Morales Reyes; Tomás Gomes Reis Veloso; José Maria Rodrigues da Luz; Monalisa Araujo Aziz; Martín Alejandro Bolaños González; Marliane de Cassia Soares da Silva (Archives of Microbiology, 2026)
The method used to preserve samples prior to DNA extraction is crucial for the accurate characterization of microbial diversity. This study evaluated the effects of different storage conditions on microbial DNA preservation in Coffea arabica fruit samples. Coffee cherries were harvested directly from plants, placed in plastic tubes, and stored at 4 °C before being subjected to four treatments: lyophilization, cryopreservation at − 80 °C, and refrigeration at 4 °C. Samples were stored for 3 and 13 days. Microbial communities were characterized by next-generation sequencing. Lyophilization retained more than 80% of the ASVs shared between days 3 and 13 of storage, whereas refrigeration at 4 °C retained less than 50%. These findings demonstrate that preservation method significantly affects the integrity of bacterial and fungal microbiomes in C. arabica beans. The absence of a time-zero control, chemical preservative comparisons, and the study’s limited scope (single variety, location, and short storage period) warrant cautious interpretation of the findings. Although lyophilization was the best-performing physical preservation strategy evaluated here, broader validation across coffee cultivars, environments, and storage durations is still required before it can be considered a standard preservation protocol for preserving microbial materials derived from coffee samples.

Bridging the biophysical gap of Water-Energy-Carbon nexus in agricultural systems: A unified emergy-based framework for evaluating regenerative and demand-side interventions - Shah Dehrai Bibi; Gengyuan Liu; Syed Aziz Ur Rehman; Ruiyan Ni; Ni Xue; Riaz Ahmad; Maria Stella Burgio; Sergio Ulgiati (Journal of Cleaner Production, 2026)

Lead and cadmium contamination in soils: impacts and phytoremediation strategies using ornamental plants, nanoparticles, and organic growth regulators - Sumbal Ammara; Muhammad Tariq Rafiq; Basharat Ali; Rukhsanda Aziz; Maria Aziz (Environmental Monitoring and Assessment, 2026)

Heavy Metals Bioaccumulation in Riparian Vegetation: A Multi-Species Biomonitoring Framework Using Total X-Ray Reflection Fluorescence Spectroscopy - Shakeel Ahmed Talpur; Simonetta Cristina Di Simone; Aziz Ahmed; Hafeez Ahmed Talpur; Muhammad Yousuf Jat Baloch; Francesco Stoppa; Luigi Menghini; Beatrice Maria Sole Giambastiani; Gianluigi Rosatelli (Environmental Processes, 2026)
Heavy metal contamination in Mediterranean riparian ecosystems presents serious risks to biodiversity and human health, requiring innovative biomonitoring methods for polluted watersheds. This study developed a comprehensive biomonitoring framework for an industrially impacted Mediterranean river basin, with approximately 100,000 tons of contaminated waste in landfills from decades of metallurgical processing. We investigated heavy metal bioaccumulation patterns in five taxonomically diverse native riparian species ( Equisetum arvense , Laurus nobilis , Rubus ulmifolius , Sambucus nigra , and Salix alba ) across contaminated and reference sites using Total Reflection X-ray Fluorescence (TXRF) spectroscopy. TXRF was validated against Inductively Coupled Plasma Atomic Optical Spectroscopy (ICP-AOS) using standard reference materials, demonstrating superior sensitivity for trace element detection in plant matrices. Heavy metal concentrations varied significantly among species and sites in riparian vegetation, with Fe (23.14 ± 5.21 mg/kg), Mn (2.74 ± 0.89 mg/kg), and Cr (3.33 ± 1.12 mg/kg) showing the highest accumulation. Laurus nobilis appeared as a multi-metal hyperaccumulator with the highest Pollution Load Index (PLI = 2.67) and exceptional accumulation of Cr (14.74 mg/kg) and Fe (63.64 mg/kg). Statistical analysis (Kruskal-Wallis test, p < 0.05) confirmed that Mn and Cr represented primary anthropogenic pollutants, with contaminated sites showing 2.20-fold and 1.92-fold increases, respectively. Principal Component Analysis revealed distinct co-accumulation networks, with Fe-Cr-Ni-Cu forming synchronized uptake mechanisms, while Mn operated independently. Biogeochemical ratio analyses (Fe/Zn, Cu/Mn) provided sensitive contamination indicators, detecting physiological stress beyond simple concentration measurements. Results support species-specific phytoremediation strategies aligned with UN Sustainable Development Goals, with Laurus suitable for multi-metal extraction and Equisetum for Mn-specific remediation, advancing sustainable environmental management in industrially impacted Mediterranean watersheds.

Exploring Nitrogen Use Efficiency in Cereals: Insight into Traits, Metabolism, and Management Strategies Under Climate Change Conditions – A Comprehensive Review - Fatima Zahra Ben Debbane; Aziz Baidani; Maria Aarbaoui; Rachid Moussadek; Rachid Mrabet; Ali Amamou (Journal of Soil Science and Plant Nutrition, 2025)

Enhancing Efavirenz Bioavailability Via Polymer-Based Buccal Administration: Optimization and Characterization of Nanocrystal-Loaded Dissolving Microneedle Delivery Systems - Khairiyah Khairiyah; Muh. Bisfain Asaf; Nur Afni Annisa Achmad; Rachmatya W. Tuna; Irfan Kurniawan; Anugerah Yaumil Ramadhani Aziz; Maria Mir; Juan Domínguez-Robles; Mónica Millán-Jiménez; Ilyas Essadki-Aittaji; Ana B. Cobo-González; Muhammad Aswad; et al. (The AAPS Journal, 2025)

Economic valuation of cultural services at the Todgha Oasis, Morocco - M'hamed Ahrabous; Khalil Allali; Aziz Fadlaoui; Fatima Arib; Maria Dolores de-Miguel; Francisco Alcon (Journal for Nature Conservation, 2023)

Facile fabrication of flexible ceramic nanofibrous membranes for enzyme immobilization and transformation of emerging pollutants - Dan Zhao; Maria Louise Leth; Maher Abou Hachem; Iram Aziz; Natalija Jančič; Thomas Luxbacher; Claus Hélix-Nielsen; Wenjing Zhang (Chemical Engineering Journal, 2023)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Mapping global cropland and field size - Steffen Fritz; Linda See; Ian McCallum; Liangzhi You; Andriy Bun; Elena Moltchanova; Martina Duerauer; Fransizka Albrecht; Christian Schill; Christoph Perger; Petr Havlik; Aline Mosnier; et al. (Global Change Biology, 2015)
A new 1 km global IIASA ‐ IFPRI cropland percentage map for the baseline year 2005 has been developed which integrates a number of individual cropland maps at global to regional to national scales. The individual map products include existing global land cover maps such as GlobCover 2005 and MODIS v.5, regional maps such as AFRICOVER and national maps from mapping agencies and other organizations. The different products are ranked at the national level using crowdsourced data from Geo‐Wiki to create a map that reflects the likelihood of cropland. Calibration with national and subnational crop statistics was then undertaken to distribute the cropland within each country and subnational unit. The new IIASA ‐ IFPRI cropland product has been validated using very high‐resolution satellite imagery via Geo‐Wiki and has an overall accuracy of 82.4%. It has also been compared with the EarthStat cropland product and shows a lower root mean square error on an independent data set collected from Geo‐Wiki. The first ever global field size map was produced at the same resolution as the IIASA ‐ IFPRI cropland map based on interpolation of field size data collected via a Geo‐Wiki crowdsourcing campaign. A validation exercise of the global field size map revealed satisfactory agreement with control data, particularly given the relatively modest size of the field size data set used to create the map. Both are critical inputs to global agricultural monitoring in the frame of GEOGLAM and will serve the global land modelling and integrated assessment community, in particular for improving land use models that require baseline cropland information. These products are freely available for downloading from the http://cropland.geo-wiki.org website.

Understanding the biology of ex vivo-expanded CD8 T cells for adoptive cell therapy: role of CD62L - C. Marcela Díaz-Montero; Abdel-Aziz Zidan; Maria F. Pallin; Vasileios Anagnostopoulos; Mohamed L. Salem; Eric Wieder; Krishna Komanduri; Alberto J. Montero; Mathias G. Lichtenheld (Immunologic Research, 2013)

Genetic and morphological characterization of chestnut (Castanea sativa Mill.) germplasm in Piedmont (north-western Italy) - Daniela Torello Marinoni; Aziz Akkak; Chiara Beltramo; Paolo Guaraldo; Paolo Boccacci; Giancarlo Bounous; Anna Maria Ferrara; Andrea Ebone; Elena Viotto; Roberto Botta (Tree Genetics & Genomes, 2013)